2021
DOI: 10.1080/2000656x.2021.1962333
|View full text |Cite
|
Sign up to set email alerts
|

Modified Frailty Index (mFI) predicts 30-day complications after microsurgical breast reconstruction

Abstract: Frailty lacks a universal definition. The modified Frailty Index (mFI) using patient comorbidities can be used to measure frailty. We hypothesized that mFI predicts 30-day complications after microsurgical breast reconstruction. American College of Surgeons' (ACS) National Surgical Quality Improvement Project (NSQIP) was investigated to identify patients undergoing microsurgical breast reconstruction between 2005-2014 using Current Procedure Terminology (CPT) code, 19364. We used mFI as a measure of frailty. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…We also found age (OR 1.08, 95%CI 1.02-1.15; P = 0.009) and operation time (OR 1.01, 95%CI 1.00-1.0; P < 0.001) were also independently associated with complications. This was consistent with the finding by Osaid Alser et al [20] that operation time was an independent predictor of infection complications in 4197 patients who underwent ICF repair, and that Barkat Al et al [21] found an independent predictor of total complications with an age of 30 days in 3237 patients undergoing microsurgical breast reconstruction. However, in 10,550 patients who underwent free flap breast reconstruction, David A. Magno-Pardon [22] et al found that body weight index greater than 30 kg/m 2 (OR 1.45; 95%CI,1.31-1.61 ;p < 0.001) was an independent predictor of complications.…”
Section: Discussionsupporting
confidence: 89%
“…We also found age (OR 1.08, 95%CI 1.02-1.15; P = 0.009) and operation time (OR 1.01, 95%CI 1.00-1.0; P < 0.001) were also independently associated with complications. This was consistent with the finding by Osaid Alser et al [20] that operation time was an independent predictor of infection complications in 4197 patients who underwent ICF repair, and that Barkat Al et al [21] found an independent predictor of total complications with an age of 30 days in 3237 patients undergoing microsurgical breast reconstruction. However, in 10,550 patients who underwent free flap breast reconstruction, David A. Magno-Pardon [22] et al found that body weight index greater than 30 kg/m 2 (OR 1.45; 95%CI,1.31-1.61 ;p < 0.001) was an independent predictor of complications.…”
Section: Discussionsupporting
confidence: 89%
“…8 Frailty, a measure of physiological reserve, broadly defined as the cumulative burden of baseline comorbid conditions and functional status impairment, has been associated with worse postoperative outcomes across surgical subspecialties. [9][10][11][12][13] In recent years, several studies have assessed the impact of baseline frailty status on postoperative outcomes in patients undergoing spine surgery, 14 though its application to spine trauma and TSI has been limited to 2 studies. 15,16 The lack of large scale, high quality, clinical studies on frailty and spine trauma has been emphasized before.…”
Section: Neurospine Eissn 2586-6591 Pissn 2586-6583mentioning
confidence: 99%
“…[11][12][13] The mFI has been shown to be valuable in identifying at-risk populations and in predicting the risk of morbidity and mortality for various cancerrelated operations. 14,15 Sarcopenia, defined as loss of skeletal muscle mass and function, has also emerged as a relevant predictor of outcomes and risk of complications among cancer patients. [16][17][18] Sarcopenia has been shown to be a predictor of adverse outcomes across multiple surgical and medical fields including gastric cancer, colorectal cancer, and oropharyngeal squamous cell carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…The modified frailty index (mFI) is a measure of 11 variables from the American College of Surgeons National Surgical Quality Improvement Project (ACS‐NSQIP) that defines decreased physiologic reserve, or frailty, in surgical patients 11–13 . The mFI has been shown to be valuable in identifying at‐risk populations and in predicting the risk of morbidity and mortality for various cancer‐related operations 14,15 …”
Section: Introductionmentioning
confidence: 99%